Assesment the Trend of Climatic Changes in Neishabur Plain Based on Temperature and Precipitation Extreme Weather Index - Marjan Ghoochanian; Hossein Ansari; Abolfazl Mosaedi (Nīvār)
In recent years, due to the decrease in percipitation, attention to climate change and the economic, social consequences and financial damages related to extreme index have become very important. Therefore, it seems necessary to investigate the continuation of meteorological and rainfall limit indicators in the long-term statistical period and to determine the climate of different regions of the country. In this research, 28 extreme meteorological and precipitation indices were calculated and SU, TR, TXx, TNx, ID and TXn in 99% confidence level and SDII and R10mm indices in 95% confidence level and TN90p, WSDI, FD, R95p indices and PRCPTOT were significant in 90% confidence level. According to the trend of hot, cold and precipitation extreme indices in this research, the precipitations have generally become shorter and more intense. In such a situation, part of the water resulting from the precipitation turns into runoff and quickly becomes unavailable. The increase in hot and cold extreme indices has changed the type of precipitation from snow to rain, which reduces the opportunity to store water from precipitation, as well as increasing evapotranspiration and faster loss of renewable water resources. De Martonne and Emberger climate classification was used to investigate the changes in the region. Finally, the relationship between the trend of these indicators and climate classifications using the De Martonne method and the Emberger climate map for Neyshabour Plain was investigated and analyzed, and the results showed that these two classification methods do not match with the trend of extreme weather index.